Protective effect of yacon leaves extract (Smallanthus sonchifolius(Poepp.) H. Rob) through antifibrosis, anti-inflammatory, and antioxidant mechanisms toward diabetic nephropathy - Wahyu Widowati; Rita Tjokropranoto; Philips Onggowidjaja; Hanna Sari Widya Kusuma; Cahyaning Riski Wijayanti; Meganita Marthania; Afif Yati; Rizal Rizal (Wolters Kluwer Medknow Publications, 2023)
Background and purpose: Diabetic nephropathy (DN) is a chronic kidney failure, which may lead to fatality. Mesangial cell proliferation, renal inflammation, stress oxidative, and fibrosis are involved in DN progression. Yacon leaves (Smallanthus sonchifolius (Poepp.) H. Rob.) contains large amounts of phenolic compounds and it has the ability to inhibit oxidative stress, inflammation, and fibrosis. Considering the potential of yacon leaves extract (YLE), it may be used for DN treatment. This research aimed to elucidate YLE's potential as anti-DN through anti-inflammatory, antioxidant, and antifibrosis mechanisms. Experimental approach: Mesangial cells were induced by glucose 20 mM for 5 days and treated with YLE concentrations as much as 5, 10, and 50 µg/mL. TGF-β1, TNF-α, and MDA levels were measured using the ELISA method. SMAD2, SMAD3, SMAD4, and SMAD7 gene expressions were analyzed using the qRT-PCR method. Findings/Results: YLE at 5, 10, and 50 µg/mL could reduce the levels of TGF-β1, TNF-α, and MDA compared with the DN cells model. YLE could reduce gene expressions of SMAD2, SMAD3, and SMAD4 and increase SMAD7 expression. Conclusion and implications: YLE potentially mitigated diabetic nephropathy through antifibrosis, anti-inflammatory, and antioxidant capacities.